Pembangunan Sistem Informasi Point of Sale Terintegrasi berbasis Web (Studi Kasus : MangoSaurus, Taichan.otw, dan RinduCandu) - Muhammad Rizqi Rakha Aulia; Komang Candra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The number of ideas in making a culinary business makes a lot of competition in the sale of these products, there is many individuals make several businesses that are managed alone. Muhammad Farchan Rafsanjani is one of the many people who have several businesses, including MangoSaurus which sells juice products, RinduCandu which sells drink products, and Taichan.otw which sells satai taichan products. With so many businesses running, of course management is a very important thing. However, the daily transaction recapitulation system that is run in his businesses uses books, the recapitulation carried out on the books is not reliable, and sometimes the money earned on certain days is more than the number of transactions in the recapitulation. The stock management in the three businesses is considered very ineffective, the empty stock will be reported by employees to the owner via chat on social media applications, so the owner goes back and forth to add stock to each of his businesses. Therefore, this study builds an integrated Point of sale (POS) information system that can display daily transactions and various types of management. The development process in this research uses the waterfall method. This system is website-based using the PHP programming language and the CodeIgniter framework. In the part of testing, whitebox testing was carried out for unit and integration testing, after that blackbox testing was carried out which resulted in a validity value of 100%, and the last was performance testing which resulted in an average loading time of 2.579 seconds.